Inventory and hinge entangled fields of research in the arts : Institute for Contemporary Art Research 2001-2022 - Schenker, Christoph 1957- (Diaphanes, 2022)
Inventory and Hinge provides an overview of the research projects performed over the last two decades at the Institute for Contemporary Art Research (IFCAR) of Zurich University of the Arts (ZHdK). It is an inventory because it presents all the projects realized during this period with many figures and illustrations. It is a hinge because links and QR codes grant access to nearly all publications and websites that were created by the individual projects. Artistic work interconnects multiple competencies and areas of knowledge, ways of life and working, and the IFCAR research projects are thus organized in correspondence with this transgressive gesture, which becomes manifest here as interdisciplinary, networked knowledge production. The cultivation of these complexities has been a mission of the IFCAR since its inception. Throughout these pioneering years the IFCAR has always seen its task in the promotion of research competency in the fine arts, and in providing support for the conception and execution of concrete projects. Although art as research has a long tradition outside of institutions, this task meant nothing less than introducing a new research discipline into the context of knowledge and establishing a new genre in the context of art. Each of the projects presented in this book involves research through the process of creation—but they often also conduct a metadiscourse on artistic research itself
Keywords: Institute for Contemporary Arts Research -- Zürich; Geschichte 1960-2022; Geschichte; Geschichte 1999-2022; Fotografie; Kunst; Videokunst; Forschungsprojekt; Bildband